1961
DOI: 10.1084/jem.114.6.837
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Formation in Vitro

Abstract: The successful initiation of a primary antibody response in tissue culture has been reported by several workers (1--4). I n a previous report from this laboratory (3) it has been suggested that the sequential action of at least two different types of cells was responsible for the formation of antibody in tissue culture. One type was a mononucleated cell with phagocytic activity, referred to as a macrophage, and the other was a non-phagocytic cell belonging to the lymphocytic series. The macrophage, presumably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
100
0
2

Year Published

1967
1967
1974
1974

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 393 publications
(108 citation statements)
references
References 18 publications
6
100
0
2
Order By: Relevance
“…The evidence favoring an eminent role for the macrophage in the induction of the immune response has been well documented and has accrued from both in vitro and in vivo investigations (36)(37)(38)(39)(40)(41)(42). However, the exact stage in the immune response where the macrophage acts has hitherto not been precisely stated or defined.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence favoring an eminent role for the macrophage in the induction of the immune response has been well documented and has accrued from both in vitro and in vivo investigations (36)(37)(38)(39)(40)(41)(42). However, the exact stage in the immune response where the macrophage acts has hitherto not been precisely stated or defined.…”
Section: Discussionmentioning
confidence: 99%
“…These latter studies were performed with a bacterial antigen (Shigella) and still remain to be confirmed and repeated with protein antigens. The difference in effectiveness of X-ray on tissue receiving antigen immediately as compared to tissue receiving antigen 12-24 hr later, could possibly be explained on the basis of an inhibitory effect of irradiation on a unique antigen-processing function of macrophages (29,30). If this were the case, however, it is clear that the irradiated macrophages must lose this special property over a period of 12-24 hr after irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…The size may affect the period within the body during which an antigen may retain its configuration and may also affect the rate at which it is phagocytized. Whether such phagocytosis is itself an active step in the initiation of the immune response (37,38) it simply serves to reduce the ambient antigen concentration in the immediate surroundings of antibody-forming cells must remain open. Promoting capacity of cells does not solely depend on size of the antigen: the promoting capacity of red blood corpuscles and nucleated cells shows considerable differences.…”
Section: Discussionmentioning
confidence: 99%